Inhibits potency of bitter leaves (Vernonia amygdalina delile) Ethanolic extract on Nickel Ion release from Orthodontic stainless- Steel Bracket : An in vitro study - Bahirrah, Siti; Ilyas, Syafruddin; Narmada, I.B.; Lestari, Widya (Ectodermal Dysplasia Group – Turkey, 2024)
Stainless steel orthodontic bracket was chosen by orthodontists because of its good resistance to corrosion properties, but corrosion followed by ion nickel release may be higher because of using mouthwash products. An adverse effect of nickel ion released induced a hypersensitivity reaction to toxicity. Organic inhibitors are used to inhibit an excessive corrosion reaction, such as Bitter leaves extract that contains many bioactive substances as an organic inhibitor. This study aimed to measure inhibits potency of ion nickel release from stainless steel orthodontic brackets immersed in saliva artificial, chlorhexidine, and Bitter leaves extract. Twentyfive stainless steel orthodontic brackets immersed in artificial saliva, chlorhexidine, 1,56 mg/ml Bitter leaves ethanolic extract, 3,125 mg/ml Bitter leaves ethanolic extract, and 6,25 mg/ml Bitter leaves ethanolic extract. Nickel ion released was analyzed by the Inductively Couple Plasma Mass Spectrometry (ICP-MS). The result of average daily ion nickel released for 7 days on 5 groups showed ion nickel release higher in the group immersed by chlorhexidine. Ion nickel releases are lowest in the group immersed by 3,56 mg/ml of bitter leaves extract. Bitter leaves extract had a potency as an organic inhibitor towards ion nickel release. A higher concentration of extract would increase and inhibits potency.